Guiding Principles from Sūrah Al-Kahf For the Development of The Islamic Identity of Muslim Youth - Gaya, Shahbaz; Ahmad, Nadzrah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract This study aims to derive guiding principles from Sūrah al-Kahf for Muslim youth to preserve and develop their Islamic identity. An inductive approach was used to analyse the four major narratives of the sūrah: the companions of the cave, the companion of the two gardens, Mūsa and Khiḍr, and the narrative of Dhū al-Qarnayn. Through this process, the study extracted seven guiding principles for developing the Islamic identity of Muslim youth. These guiding principles deal specifically with the major threats faced by Muslim youth in preserving their Islamic identity. Through the first narrative, the companions of the cave, four guiding principles were extracted relating to the threats of peer pressure, assimilation, and Islamophobia. The second narrative of the companion of the two gardens provided a principle in dealing with materialism and corrupt desires. The third narrative of Mūsa and Khiḍr was the source of a principle dealing with the threats of religious doubt and the loss of religion in society. The fourth and final narrative of Dhū al-Qarnayn personified the application of all the previous principles illustrating the importance of providing Muslim youth with an exemplary role model. These seven guiding principles provide applicable solutions that can be used to protect and develop the Islamic identity against specific threats. This study serves as a crucial step in finding solutions to the challenges and threats faced by Muslim youth in preserving their Islamic identity. If followed sincerely, these principles can empower Muslim youth by transforming them into confident and successful leaders through their Islamic identity, ensuring their success in this world and the hereafter.